2022
DOI: 10.3390/cells11213453
|View full text |Cite
|
Sign up to set email alerts
|

A Linkage between Angiogenesis and Inflammation in Neovascular Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of visual impairment in the aging population with a limited understanding of its pathogenesis and the number of patients are all the time increasing. AMD is classified into two main forms: dry and neovascular AMD (nAMD). Dry AMD is the most prevalent form (80–90%) of AMD cases. Neovascular AMD (10–20% of AMD cases) is treated with monthly or more sparsely given intravitreal anti-vascular endothelial growth factor inhibitors, but unfortunately, not all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 120 publications
2
27
0
Order By: Relevance
“…With the increasing elderly population, visual impairment is to be anticipated 18 . Currently, cataract surgery remains as the leading eye surgeries specifically in the aging population 6,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing elderly population, visual impairment is to be anticipated 18 . Currently, cataract surgery remains as the leading eye surgeries specifically in the aging population 6,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Our review can also be a basis for the informed consent with patients and medical team before and after cataract surgery. It is also important to identify the risk factors of cataract surgery and AMD, as both share similar risk factors such as age, sex, ethnicity, and the signs of AMD before and after surgery 10,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant progress in understanding the molecular mechanisms of AMD and ongoing therapeutic clinical trials, a definitive cure for AMD is still not publicly available. Currently, the only treatment option involves the use of anti-vascular endothelial growth factor (anti-VEGF) drugs, administered through intravitreal injections, to slow the progression of wet AMD (Heloterä & Kaarniranta, 2022). Encouragingly, recent observations regarding complement inhibitors offer hope for patients suffering from GA (Goldberg et al, 2022;Khan et al, 2023;Khanani et al, 2023).…”
Section: Conc Lusionsmentioning
confidence: 99%
“…14 Angiogenic factors can induce retinal neovascularization, leading to inflammation, endothelial cell differentiation, and recruitment of T-cells and macrophages to the damaged site. 15,16 Angiotensin II initiates responses via G protein-coupled receptors known as AGTR2 (Angiotensin II receptor type-II), which include AT1R and AT2R. Research has shown that AT1R-induced angiogenesis can produce a significant increase in pro-inflammatory cytokines, 17 whereas AT2R was found to be antagonistically reduced angiogenesis.…”
Section: Introductionmentioning
confidence: 99%